A rare case report of vulvar necrotizing fasciitis in a healthy patient. (2017) - Patel, Takshaka; Kothari, Rajul; Gangemi, Antonio
Highlights: NF should be considered regardless of atypical location and lack of associations. Clinical findings are important indicators when diagnosing NF. Immediate surgical intervention should be performed upon suspicion of NF. Abstract: Introduction: Necrotizing fasciitis (NF), a necrotizing infection of the soft tissue, is a medical emergency usually occurring in the lower extremities and abdominal regions and often difficult to diagnose promptly. Presentation of case: This case report looks at one atypical presentation of NF with the unusual location of the vulva and no known associated comorbidities or risk factors. Discussion: Diagnosing this patient was particularly difficult due to the inconsistent clinical, laboratory and imaging findings. The CT scans and WBC count were indicative of NF, but the LRINEC score was not high enough to make the diagnosis of NF. As a result, we relied on the hemodynamic instability and clinical findings of the physical exam to be strong indicators of NF, and acted on that indication. Conclusion: Acting quickly on the hemodynamic findings and suspicion as opposed to waiting for a confirmed diagnosis resulted in a good prognosis since immediate surgical debridement is imperative to surviving this acute condition. Despite major advancements in the imaging modalities and the introduction of a laboratory score, our case suggests that the diagnosis still heavily relies on clinical findings, such as hemodynamic instability. Furthermore, our case suggests that NF should be included in the differential regardless of atypical location and lack of common clinical associations.